1999
DOI: 10.1590/s1415-47571999000400005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular analysis of spinal muscular atrophy in Brazilian patients

Abstract: Spinal muscular atrophy (SMA), the second most common lethal autosomal recessive disorder, has an incidence of 1:10,000 newborns. SMA is divided into acute (Werdnig-Hoffmann disease, type I), intermediate (type II) and juvenile forms (KugelbergWelander disease, type III). The gene of all three forms of SMA maps to chromosome 5q 11.2-13.3. Two candidate genes, the survival motor neuron (SMN) gene and the neuronal apoptosis inhibitory protein (NAIP) gene, have been identified; SMN is deleted in most SMA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…In 5 patients, age at onset was before 18 months, which is characteristic of type II SMA , while walking capacities were compatible with SMA type III. Coexistence of various types of SMA (II and III) within a given family occurred in our series (2/57 families), as reported elsewhere [ 33 , 34 ], in favor of a continuous spectrum in childhood SMA . Additionally we found a predominance of males to females (17 female/36 males) in type III SMA , as previously reported by Rudnik-Schöneborn et al who suggested the presence of a female sparing factor [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…In 5 patients, age at onset was before 18 months, which is characteristic of type II SMA , while walking capacities were compatible with SMA type III. Coexistence of various types of SMA (II and III) within a given family occurred in our series (2/57 families), as reported elsewhere [ 33 , 34 ], in favor of a continuous spectrum in childhood SMA . Additionally we found a predominance of males to females (17 female/36 males) in type III SMA , as previously reported by Rudnik-Schöneborn et al who suggested the presence of a female sparing factor [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…Taking the three subgroups together, the total frequency of deletions (90%) was similar to other studies reported from other populations from China, 12 Germany, 13 Japan, 14 Spain, 15 Singapore 16 and the United States. 17 A lower proportion of deletions, however, ranging from 57% to 85%, was reported in other studies in Brazil, 18 Canada, 19 Malaysia 20 and Turkey. 21 Deletions involving both exons 7 and 8 (84%) were much more frequent than deletions of only exon 7 (5.3%) or only exon 8 (1.3%).…”
Section: Discussionmentioning
confidence: 83%
“…Kim et al [28] characterized the genotype of Brazilian patients with SMA, but they did not evaluate the carrier frequency of the deleted SMN1 gene in nonrelated and healthy Brazilians with no family history of SMA.…”
Section: Discussionmentioning
confidence: 99%